Hubungan Gaya Kepemimpinan dan Motivasi dengan Kinerja Pegawai: Perspektif Aparatur Sipil Negara di Kementerian Agama Kota Tangerang Selatan - Winata, Hadi; Sutrisno, Sutrisno; Paeno, Paeno (LAP4B, 2025)
This study aims to analyze the influence of leadership style and motivation on employee performance at the Office of the Ministry of Religion of South Tangerang City. The research method used an associative quantitative approach with saturated sampling techniques, involving the entire population of 63 employees. Data collection was carried out through questionnaires using various statistical analysis techniques, including validity, reliability, normality, and regression tests. The results showed that leadership style had a significant effect on employee performance, with a tcal value (7,620) > ttable (1,999) and a significance of 0.000 < 0.05. Similarly, work motivation has a significant influence on performance, with a tcal value (14,904) > ttable (1,999) and a significance of 0.000 < 0.05. Simultaneous testing showed that leadership style and motivation together had a significant influence on employee performance, with a value of Fcal (120.183) > Ftable (3.15) and significance of 0.000 < 0.05. A determination coefficient value (R Square) of 0.895 indicates that leadership style and motivation contribute 80% to employee performance, while the remaining 20% is influenced by other factors outside the research model. The findings of this study provide important implications for the development of human resources within the Ministry of Religion, especially in efforts to improve the performance of the state civil apparatus through the optimization of leadership style and work motivation.